2020
DOI: 10.1017/s1368980020001779
|View full text |Cite
|
Sign up to set email alerts
|

Dishing on dinner: a life course approach to understanding the family meal context among families with preschoolers

Abstract: Objective: Family meals promote healthful dietary intake and well-being among children. Despite these benefits, family meal participation typically declines as children age. This study utilises life course theory to explore parents’ perceptions of family meals in order to understand how parents’ past experiences with family meals (in childhood and earlier in adulthood) influence their current beliefs and practices regarding mealtimes with their own children. Design: Semi-structured quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…Sixteen studies conducted across North America [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ], Europe [ 50 , 51 , 52 , 53 ] and Australia [ 54 , 55 , 56 , 57 ] were included in this metasynthesis. Sample sizes ranged from 8 participants [ 40 ] to 149 participants [ 47 ], with studies exploring the perspectives of fathers, mothers and families.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sixteen studies conducted across North America [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ], Europe [ 50 , 51 , 52 , 53 ] and Australia [ 54 , 55 , 56 , 57 ] were included in this metasynthesis. Sample sizes ranged from 8 participants [ 40 ] to 149 participants [ 47 ], with studies exploring the perspectives of fathers, mothers and families.…”
Section: Resultsmentioning
confidence: 99%
“…Meal-related tasks (particularly meal preparation) were shared between couples in an attempt to reduce the burden of domestic duties on the primary caregiver [ 40 , 42 , 46 , 51 , 53 , 55 , 57 ]. Some fathers also recognised that in adopting a shared feeding approach with their partner, they were able to collectively identify and use strategies to respond to the challenges posed by food fussiness [ 46 , 48 , 53 , 54 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During snack time, children and educators sit at the table, which is a positive attitude towards food [62,63]. For instance, a study by Wansink and Kleef [64] showed lower Body Mass Indexes (BMI) among parents and children of families who had dinner daily sitting at the table in relation to families who ate in other places, highlighting the act of sitting at the table as a practice of social support and family involvement being a possible strategy to fight obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, parental food parenting practices may impact the emotional climate of mealtimes with young children (Hughes et al, 2011). It has been suggested that negative feelings about family mealtimes with preschoolers (e.g., being viewed as 'fraught') may be related to parents wanting to control their child's food intake during that time (Walton et al, 2021(Walton et al, , p. 1343). However, importantly, it is maternal-and not child-emotions that appear to determine the mealtime emotional climate, and which are also linked with food involvement parenting practices and the child's consumption of healthy foods (Saltzman et al, 2018).…”
Section: Introductionmentioning
confidence: 99%